Refund Akibat Pembatalan Tiket Pesawat sebagai Dampak Pandemi Covid-19 - Rory Jeff Akyuwen (Faculty of Law, Universitas Pattimura, 2021)
As a result of events experienced by almost the entire world, namely the outbreak of the Covid-19 pandemic which caused almost all public facilities for sea and air transportation to be closed unilaterally by the local government, one of which is that airlines unilaterally cancel airplane tickets to consumers due to the outbreak of the Cocid-19 pandemic. The purpose of this study is to examine the impact that occurs on flight ticket cancellations due to the Covid-19 pandemic. The research method used in this research is normative legal research which is descriptive analysis based on secondary data. The results show that transportation policies during the Covid-19 pandemic have been regulated in laws and regulations related to transportation control in order to prevent the spread of the Covid 19 Virus which has an impact on the unilateral cancellation of airplane tickets by airlines as the reason for Force Majeure because it is a non-natural event. which is unexpected, so this is the responsibility of the airline as a business actor for compensation to consumers for cancellation of plane tickets due to the Covid 19 pandemic on a refund in the form of a full refund (100%) or in the form of airplane ticket vouchers.